MAHAR DAN PROBLEMATIKANYA (Sebuah Telaah Menurut Syariâat Islam) - Shuhufi, Muhammad (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
This article discussed the problems of dowry and wisdom of dowry in marriage. Based on some of the arguments of both the Koran and the Hadits, dowry is understood as a wifeâs financial rights which are the duty of man. Dowry is classified into musamma and misil. The greatest wisdom of dowry declaration for a man is as a respect for the humanity of women. Dawry is also a symbol of husbandâs love given to his wife. Dawry is a sign of sincerity of a man being in charge and protector for wife.